Health workforce contributions to health system development: a platform for universal health coverage - Viroj Tangcharoensathien; Supon Limwattananon; Rapeepong Suphanchaimat; Walaiporn Patcharanarumol; Krisada Sawaengdee; Weerasak Putthasri (The World Health Organization, 2013)
Problem In the 1970s, Thailand was a low-income country with poor health indicators and low health service coverage. The local health infrastructure was especially weak. Approach In the 1980s, measures were initiated to reduce geographical barriers to health service access, improve the health infrastructure at the district level, make essential medicines more widely available and develop a competent, committed health workforce willing to service rural areas. To ensure service accessibility, financial risk protection schemes were expanded. Local setting In Thailand, district hospitals were practically non-existent in the 1960s. Expansion of primary health care (PHC), especially in poor rural areas, was considered essential for attaining universal health coverage (UHC). Nationwide reforms led to important changes in a few decades. Relevant changes Over the past 30 years, the availability and distribution of health workers, as well as their skills and competencies, have greatly improved, along with national health indicators. Between 1980 and 2000 coverage with maternal and child health services increased substantially. By 2002, Thailand had attained UHC. Overall health system development, particularly an expanded health workforce, resulted in a functioning PHC system. Lessons learnt A competent, committed health workforce helped strengthen the PHC system at the district level. Keeping the policy focus on the development of human resources for health (HRH) for an extended period was essential, together with a holistic approach to the development of HRH, characterized by the integration of different kinds of HRH interventions and the linking of these interventions with broader efforts to strengthen other health system domains.